Industrial development in small islands economies. A comparative study of Mauritius and La Reunion growth performances - Michel Dimou (European Regional Science Association (ERSA), 2004)
Small islands economic development may follow different pathways, according to the particular combination of growth mechanisms. A comparative study of the long term growth in Mauritius and in La Reunion, two islands with strong historical, sociological and cultural links, shows that they are engaged in two different process of industrialization. La Reunion has
Keywords: 330